2014
DOI: 10.1007/s00296-013-2932-8
|View full text |Cite
|
Sign up to set email alerts
|

HLA-DRB1 and HLA-DQB1 allele associations in an Albanian patient population with rheumatoid arthritis: correlations with the specific autoantibody markers and inter-population DRB1 allele frequency variability

Abstract: The prevalence of rheumatoid arthritis and its specific autoantibodies varies in different populations. This variability depends on the genetic polymorphism of the immune response genes among which the HLA system plays a major role. In this context, we studied the HLA-DRB1 and HLA-DQB1 first-level allele frequencies in 100 Albanian patients with rheumatoid arthritis (RA), and taking into account their rheumatoid factor (RF) and anticitrullinated peptide antibodies (ACPA) serologic subgroups, we compared them w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
2
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 33 publications
2
2
0
Order By: Relevance
“…The increased frequencies of allele DQB1*03:01 (OR = 3.09) and DQB1*06:01 (OR = 2.54) revealed susceptible associations in RA. Our data are in concordance with the previous report that documented an increased susceptible association of alleles DQB1*03 and DQB1*05, while DQB1*06 with a protective association in Moroccan, Han, Albanian populations . The alleles DQB1*05:01 and *05:02 showed a protective association in the present study.…”
Section: Discussionsupporting
confidence: 93%
“…The increased frequencies of allele DQB1*03:01 (OR = 3.09) and DQB1*06:01 (OR = 2.54) revealed susceptible associations in RA. Our data are in concordance with the previous report that documented an increased susceptible association of alleles DQB1*03 and DQB1*05, while DQB1*06 with a protective association in Moroccan, Han, Albanian populations . The alleles DQB1*05:01 and *05:02 showed a protective association in the present study.…”
Section: Discussionsupporting
confidence: 93%
“…We also found that both alleles were statistically associated with ACPA seropositivity, which is consistent with studies in populations with different ethnicity ( 7 , 25 28 ). Furthermore, strong evidence suggests that some HLA-DRB1 alleles, including HLA-DRB1*01 , *04 , and *10 , were associated with the structural severity of RA, and were likely related to the production of ACPA by influencing the antigen presentation ( 29 , 30 ).…”
Section: Discussionsupporting
confidence: 91%
“…HLA-DRQ1*02 and *06 were found protective against RA in the Albanian population ( 28 ), while in the Kurdi population, these alleles showed a susceptible effect to RA ( 37 ). Other studies in the Turkish population failed to prove any association ( 33 ).…”
Section: Discussionmentioning
confidence: 99%
“…A recent genetic study investigated the HLA-DRB1 and HLA-DQB1 first-level allele frequencies in Albanian patients with RA, taking into account their rheumatoid factor (RF) and anticitrullinated peptide antibodies (ACPA) serologic subgroups. The study found relatively low frequencies of DRB1*04 and high DRB1*11 in the Albanian population that may explain the rather low positivity rate of ACPA and RF antibodies among Albanian patients with RA ( 20 ). Since both ACPA and RF antibodies are frequently associated with RA and causally involved in the genesis of the disease ( 21 ), the frequency of these alleles may explain the low occurrence of RA in our patients.…”
Section: Discussionmentioning
confidence: 72%